Recent progress on urban overheating and heat island research. Integrated assessment of the energy, environmental, vulnerability and health impact. Synergies with the global climate change - Santamouris, M. (Energy and buildings, 2020)
•Urban Overheating affects energy generation and demand, pollution, health and vulnerability.•It increases the energy demand for cooling and decreases the efficiency of power plants.•Rises the concentration of ground level ozone.•Increase indoor temperature in low income housing.•Increases heat related mortality and morbidity. Urban overheating is documented for more than 400 major cities in the world. Numerous experimental data show that the magnitude of the average temperature increase may exceed 4-5 C, while at the peak may exceed 10 C. Increased ambient temperatures cause a serious impact on the cooling energy consumption, peak electricity demand, heat related mortality and morbidity, urban environmental quality, local vulnerability and comfort. Synergies between urban heat island and heat waves increase further the amplitude of urban overheating The present paper reviews and reports the recent progress and knowledge on the specific impact of current and projected urban overheating in energy, peak electricity demand, air quality, mortality and morbidity and urban vulnerability. In parallel, it discusses new findings related to the characteristics and the magnitude of urban overheating, and reports and analyse the recent knowledge on the synergies between urban heat island and heat waves.